Diplomatic letters of the Malay empire of Bima and Netherlands - Che Puteh, Che Nuraini; Noor Muhammad, Salmah Jan (Human Resource Management Academic Research Society, 2018)
Letter is the eldest Malays manuscript that has been used in two ways communication since it is more formal and resembles the honesty of the senders him/herself regarding his/her motive. During the reign of past Era of Malay’s king, without sending a letter in any communication. It will depict that particular action is irrespectful. Hence, any delegation will be come together with the letter. In the meanwhile, letters must be written in well mannered and wisdom. The main objective of this research is to identify and analyze the diplomatic aspect in letters send by Bima’s Empire to Netherlands’ Empire. This research will be using the theory of Moral Diplomatic and enhanced with qualitative method. This method will analyze texts, collecting data, classifying data and conclude all those data based on their very own function. Hopefully, this research will help to identify diplomatic aspect that been used broadly in Letter during two way communication of Malay’s Empire and Netherlands’ Empire.